Visdommens lænker : Kommentarer til nogle nyere studier over 1700-tallets kristendomsundervisning - Bugge, K. E. (Kirkehistoriske Samlinger, 1990)
The Chains of Wisdom - Comments on some recentstudies in the field of18th and 19th century religious education Under the title »The Chains of Wisdom« which is a quotation from the Book of Sirach, one of the Old Testament Apocrypha, the historian Ingrid Markussen in 1989 published an extensive study on the development of Danish public education in the 18th and early 19th century. Due to the close relationship between church and school during that period this study is of considerable interest also in a perspective of church history. On this background the present review focuses on the presentation of the two dominant manuals for Christian/Religious education and on the educational influence of the apocrypha. The first manual, published by Erik Pontoppidan in 1737, represents the pietistic tradition, whereas the second manual, published by N. E. Balle in 1791, is a product of the age of enlightenment. IM’s presentation of these manuals is critically evaluated. A number of formal and factual errors are listed, and the historical context of these publications is sought understood in the wider perspective of Lutheran education. IM’s study provides new insights into the decisive role played not only by the two manuals of Pontoppidan and Balle, but also by the apocrypha. Due to a debate between representatives of the »The British and Foreign Bible Society« and their Danish counterparts during the 19th century, the traditional Lutheran practice of incorporating the apocrypha in the official version of the Bible was seriously questioned. As a result the apocrypha are usually omitted from Danish bibles in the 20th century. The actual influence of these texts on the formation of the spiritual atmosphere of former centuries has therefore been underestimated in modern research. The study of IM has demonstrated that the »Chains of Wisdom« are not only to be conceived as disciplinary measures imposed by the political powers. This negative evaluation is often found in current research. On the contrary, the stimulation of religious education towards personal development has also offered a positive, emancipatory contribution to social and political development in Denmark.